Gymnastics is easy peasy in one click / Nurhidayah Yaakop, Denise Koh and Ruhizan Mohammad Yasin - Yaakop, Nurhidayah; Koh, Denise; Mohammad Yasin, Ruhizan (2023)
Introduction: Promoting the acquisition of essential motor skills in children is crucial for enhancing their ability to engage in physical activities and lowering the likelihood of obesity. The Fundamental Movement Skills (FMS) are typically introduced in schools through the Physical Education (PE) curriculum, specifically within the context of Gymnastics teaching. However, teachers need help in teaching gymnastics due to limited reference sources. Therefore, this study aims to develop a teaching module on Gymnastics based on the Malaysian Year 5 PE curriculum. Objective: To develop a teaching module for gymnastics specifically for PE teachers in Malaysian public schools. Methodology: This research used a Design and Developmental Research (DDR) approach with two Focus Group Discussion (FGD) sessions. Then, the Fuzzy Delphi Method (FDM) was used to determine the main components in the Gymnastics Training Module. Finally, the evaluation of the usability level of the module was done using the Modified Nominal Group Technique (Modified NGT). Result: The research indicates that the Gymnastics Training Module is a valuable resource for teachers. Conclusion: This module effectively caters to the requirements of teachers in teaching Gymnastics to students. It is advisable to consider further research that assesses the impacts of the KSSR Gymnastics Training Module on teachers' knowledge and proficiency in gymnastics skills. Practical Implication: Developing support materials for teachers to conduct basic gymnastics sessions at school significantly boosts teachers' confidence, especially for non-accredited physical education teachers.